Patient-Reported Functional Outcomes After Hypofractionated or Conventionally Fractionated Radiation for Prostate Cancer: A National Cohort Study in England - Nossiter, Julie (J Clin Oncol, 2020)
PURPOSE: The aim of the current study was to determine patient-reported functional outcomes in men with prostate cancer (PCa) undergoing moderately hypofractionated (H-RT) or conventionally fractionated radiation therapy (C-RT) in a national cohort study. PATIENDS AND METHODS: All men diagnosed with PCa between April 2014 and September 2016 in the English National Health Service undergoing C-RT or H-RT were identified in the National Prostate Cancer Audit and mailed a questionnaire at least 18 months after diagnosis. We estimated differences in patient-reported urinary, bowel, sexual, and hormonal function—Expanded Prostate Cancer Index Composite short-form 26 domain scores on a 0 to 100 scale—and health-related quality of life—EQ-5D-5L on a 0 to 1 scale—using linear regression with adjustment for patient, tumor, and treatment-related factors in addition to GI and genitourinary baseline function, with higher scores representing better outcomes. RESULTS: Of the 17,058 men in the cohort, 77% responded: 8,432 men received C-RT (64.2%) and 4,699 H-RT (35.8%). Men in the H-RT group were older (age ≥ 70 years: 67.5% v 60.9%), fewer men had locally advanced disease (56.5% v 71.3%), were less likely to receive androgen-deprivation therapy (79.5% v 87.8%), and slightly more men had pretreatment genitourinary procedures (24.2% v 21.2%). H-RT was associated with small increases in adjusted mean Expanded Prostate Cancer Index Composite short-form 26 sexual (3.3 points; 95% CI, 2.1 to 4.5; P < .001) and hormonal function scores (3.2 points; 95% CI, 1.8 to 4.6; P < .001). These differences failed to meet established thresholds for a clinically meaningful change. There were no statistically significant differences in urinary or bowel function and quality of life. CONCLUSION: This is the first national cohort study comparing functional outcomes after H-RT and C-RT reported by patients. These real-world results further support the use of H-RT as the standard for radiation therapy in men with nonmetastatic PCa.